2022
DOI: 10.1186/s12969-022-00764-w
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic lymphohistocytosis in trisomy 21: successful treatment with interferon inhibition

Abstract: Background Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening condition of immune dysregulation primarily driven by the cytokine interferon gamma. It can be either a genetic or acquired disorder associated with infection, malignancy, and rheumatologic disorders. Trisomy 21 can express a wide range of phenotypes which include immune dysregulation and shares inherent pathophysiology with a group of disorders termed interferonopathies. Knowledge of this overlap in seemingly unrelated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Since autoimmunity and HLH in trisomy 21 are thought to be driven by IFN-γ, targeting interferon signaling may have potential therapeutic bene ts. 34 This study showed a signi cant role of high VD levels in decreasing IFN-γ (p-value 0.039, R 2 5.8%). VD plays an important role in regulating T helper cells as well as in the secretion of IFN-γ.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Since autoimmunity and HLH in trisomy 21 are thought to be driven by IFN-γ, targeting interferon signaling may have potential therapeutic bene ts. 34 This study showed a signi cant role of high VD levels in decreasing IFN-γ (p-value 0.039, R 2 5.8%). VD plays an important role in regulating T helper cells as well as in the secretion of IFN-γ.…”
Section: Discussionmentioning
confidence: 55%
“…11 It is estimated that individuals with DS are four to six times more likely to develop autoimmune diseases such as celiac disease, T1DM, and autoimmune thyroiditis (AITD). 8 as well as susceptibility to leukemia 12 and life-threatening conditions of immune dysregulation primarily driven by the cytokine IFN-γ, such as hemophagocytic lymphohistiocytosis (HLH) 13 . Several studies have found lower VD levels in children with DS than in children without DS [9][10][11] ; this has recently been tied to an increased risk of autoimmunity 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In mouse models of DS, both normalization of IFNR gene copy number and pharmacologic JAK1 inhibition rescue their lethal immune hypersensitivity phenotypes 22,48 . Furthermore, we recently demonstrated that IFN transcriptional scores derived from peripheral immune cells correlate significantly with the degree of immune remodeling and hypercytokinemia in DS 42 , and we and others have reported the safe use of JAK inhibitors for treatment of diverse immune conditions in DS, including alopecia areata 49 , psoriatic arthritis 50 and hemophagocytic lymphohistocytosis 51 through small case series. Encouraged by these results, we launched a clinical trial to assess the safety and efficacy of the JAK inhibitor tofacitinib (Xeljanz, Pfizer) in DS, using moderateto-severe autoimmune/inflammatory skin conditions as a qualifying criterion (NCT04246372).…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 77%
“…Emapalumab specifically targets and inhibits IFN-γ, reducing the occurrence of cytokine storms. Their combined use can regulate the immune response of patients with HLH at different levels ( 10 , 24 , 25 ). Furthermore, plasma exchange helps in clearing deposits of cytokines including IFN-γ, improving the effectiveness of emapalumab.…”
Section: International Multidisciplinary Team (Imdt) Discussionmentioning
confidence: 99%